2020
DOI: 10.2340/16501977-2648
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for improved physical and emotional functioning one year after interdisciplinary rehabilitation in patients with chronic pain: Results from a national quality registry in Sweden

Abstract: Chronic pain is a common condition that negatively affects most areas of a persons' life and is difficult to alleviate. Research indicates that interdisciplinary multimodal pain rehabilitation is effective in improving physical and emotional functioning, but little is known about the prognostic factors for a good treatment outcome. Therefore, this study investigated how different patient characteristics related to these outcomes, by following 2,876 patients across Sweden over a 1-year period. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 28 publications
2
38
0
3
Order By: Relevance
“…Our sample included 76% women (31/41), which is in line with other studies describing people with chronic pain in Sweden [65,66] and other countries [67]. Patients in our sample had lived with pain for a shorter time than what is described in other studies of this population [68,69], and they rated their pain severity at baseline as equal to what have been reported in another study [70] describing patients participating in primary care management of low back pain patients.…”
Section: Strengths and Limitationsmentioning
confidence: 53%
“…Our sample included 76% women (31/41), which is in line with other studies describing people with chronic pain in Sweden [65,66] and other countries [67]. Patients in our sample had lived with pain for a shorter time than what is described in other studies of this population [68,69], and they rated their pain severity at baseline as equal to what have been reported in another study [70] describing patients participating in primary care management of low back pain patients.…”
Section: Strengths and Limitationsmentioning
confidence: 53%
“…29 The negative influence of depression on chronic pain outcomes found in this study is consistent with previous studies. Previous studies have reported emotional distress is a risk factor of prognostic indicators for patients with chronic pain, 30 and patients with depression are more likely to suffer from chronic pain. 31 In this study, participants with depression expressed higher levels of pain severity and interference for daily life activities compared to those without depression.…”
Section: Discussionmentioning
confidence: 95%
“…Few large studies have examined the sex differences in outcomes of IMMRPs. The existing literature is conflicting: women benefit more [68,70,71], no sex differences [43,72,73], and men benefit more [74,75]. The outcomes of IMMRPs in a primary care SQRP study were better in women than in men [76].…”
Section: Sex Aspectsmentioning
confidence: 96%